A new patient‐derived iPSC model for dystroglycanopathies validates a compound that increases glycosylation of α‐dystroglycan. (30th September 2019) - Kim, Jihee; Lana, Beatrice; Torelli, Silvia; Ryan, David; Catapano, Francesco; Ala, Pierpaolo; Luft, Christin; Stevens, Elizabeth; Konstantinidis, Evangelos; Louzada, Sandra; Fu, Beiyuan; Paredes‐Redondo, Amaia; et al.
Abstract: Dystroglycan, an extracellular matrix receptor, has essential functions in various tissues. Loss of α‐dystroglycan‐laminin interaction due to defective glycosylation of α‐dystroglycan underlies a group of congenital muscular dystrophies often associated with brain malformations, referred to as dystroglycanopathies. The lack of isogenic human dystroglycanopathy cell models has limited our ability to test potential drugs in a human‐ and neural‐specific context. Here, we generated induced pluripotent stem cells (iPSCs) from a severe dystroglycanopathy patient with homozygous FKRP (fukutin‐related protein gene) mutation. We showed that CRISPR/Cas9‐mediated gene correction of FKRP restored glycosylation of α‐dystroglycan in iPSC‐derived cortical neurons, whereas targeted gene mutation of FKRP in wild‐type cells disrupted this glycosylation. In parallel, we screened 31, 954 small molecule compounds using a mouse myoblast line for increased glycosylation of α‐dystroglycan. Using human FKRP‐iPSC‐derived neural cells for hit validation, we demonstrated that compound 4‐(4‐bromophenyl)‐6‐ethylsulfanyl‐2‐oxo‐3, 4‐dihydro‐1H‐pyridine‐5‐carbonitrile (4BPPNit) significantly augmented glycosylation of α‐dystroglycan, in part through upregulation of LARGE1 glycosyltransferase gene expression. Together, isogenic human iPSC‐derived cells represent a valuable platform for facilitating dystroglycanopathy drug discovery and therapeutic development. Synopsis: Defective glycosylation of α‐dystroglycan is a pathological hallmark of secondary dystroglycanopathies that often affect the central nervous system. An unbiased screen identifies 4BPPNit that augments glycosylation of α‐dystroglycan as validated in a patient‐derived iPSC model. First human FKRP‐iPSC line was generated from a dystroglycanopathy patient with severe CNS abnormalities. Targeted gene correction of FKRP by CRISPR/Cas9 restores α‐dystroglycan glycosylation in iPSC‐derived neural cells. An unbiased high‐throughput chemical screen for increased glycosylation of α‐dystroglycan identifies 4BPPNit. 4BPPNit significantly augments glycosylation of α‐dystroglycan in human FKRP‐iPSC derived neural cells. Abstract : Defective glycosylation of α‐dystroglycan is a pathological hallmark of secondary dystroglycanopathies that often affect the central nervous system. An unbiased screen identifies 4BPPNit that augments glycosylation of α‐dystroglycan as validated in a patient‐derived iPSC model.